Mixed Oxide Supported MoO3 Catalyst: Preparation, Characterization and Activities in Nitration of o-xylene - S. M. Kemdeo; V. S. Sapkal; G. N. Chaudhari (Bulletin of Chemical Reaction Engineering & Catalysis, 2010)
TiO2-ZrO2 mixed oxide support was prepared and impregnated with 12 wt % MoO3 and calcined at various temperatures. The resultant catalyst systems were characterized by XRD, FT-IR, BET, SEM, NH3-TPD and pyridine adsorbed FT-IR methods to know the physico-chemical changes occurred in course of thermal treatment. Activities of these catalysts were tested by employing them in the nitration of o-xylene. Mostly, 500 oC calcined catalyst sample was found to be most active for nitration reaction. Catalyst calcined at higher temperatures showed the negative influence on o-xylene conversion and 4-nitro-o-xylene selectivity. Conversion can be correlated with the presence of strong Brönsted acid sites over the catalyst surface whereas change in selectivity was found attributed to the pore diameter of the catalyst. These catalysts also performed satisfactorily, when used for nitration of other aromatics. No use of corrosive sulfuric acid and efficient reusability of the catalyst make the process environmentally friendly and economic. © 2010 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)